Promise of Jak Inhibition in the Management of VEXAS, Case Report with Review of the Literature - Alnahas Z; Sarkar S; Trowell KT; Soltani L; Vasireddy S (Open Access Rheumatology: Research and Reviews, 2025)
Zeinab Alnahas,1 Sujata Sarkar,1 Kevin T Trowell,1 Lisa Soltani,2 Sreekanth Vasireddy1 1Tucson Medical Center, Tucson, AZ, USA; 2El Rio Community Health Center, Tucson, AZ, USACorrespondence: Zeinab Alnahas, Tucson Medical Center, 5301 E Grant Road, Tucson, AZ, 85712, USA, Email Zeinab.Alnahas@tmcaz.comAbstract: VEXAS syndrome (vacuoles, E1 enzyme, X-linked, autoinflammatory, somatic) is a recently described adult autoinflammatory disease associated with somatic mutations in the gene encoding ubiquitin-activating enzyme 1 (UBA1) in hematopoietic progenitor cells. Loss of function mutation of UBA1 results in a broad range of inflammatory and hematological conditions. To date, there are no established targeted therapies for VEXAS syndrome, especially in patients who are refractory to conventional immunosuppressive treatments. We report the case of a 75-year-old Hispanic gentleman with hypertension, dyslipidemia, and type 2 diabetes mellitus who presented with a 2-year history of intermittent fever, weight loss, recurrent sore throat, recurrent soft tissue swelling (mimicking cellulitis), oligoarthritis, erythema nodosum, and venous thrombosis. Laboratory workup showed elevated inflammatory markers, macrocytic anemia, and leukopenia. Patient received several rounds of antibiotics and corticosteroids for presumed cellulitis and throat infections, with limited improvement. He subsequently underwent bone marrow biopsy, which showed characteristic vacuolization of myeloid precursors. Genetic testing revealed a missense mutation in UBA1, Exon 3 c.121A>G, pMet41Val. He was diagnosed with VEXAS syndrome. He was started on corticosteroids and Tocilizumab (anti-IL-6 receptor antibody). He had severe leukopenia with Tocilizumab and was switched to Ruxolitinib (Jak inhibitor). He had a significant clinical response to Ruxolitinib and was able to be tapered off prednisone. Our case report and review of the literature report Jak inhibition as a possible target for the management of inflammatory symptoms of VEXAS.Keywords: VEXAS, autoinflammation, UBA1, genetic testing, Jak inhibition